2015
DOI: 10.1128/mcb.00161-15
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Signaling Cascade for Erythropoietin Production in Hepatocytes

Abstract: f Erythropoietin (Epo) is produced in the kidney and liver in a hypoxia-inducible manner via the activation of hypoxia-inducible transcription factors (HIFs) to maintain oxygen homeostasis. Accelerating Epo production in hepatocytes is one plausible therapeutic strategy for treating anemia caused by kidney diseases. To elucidate the regulatory mechanisms of hepatic Epo production, we analyzed mouse lines harboring liver-specific deletions of genes encoding HIF-prolyl-hydroxylase isoforms (PHD1, PHD2, and PHD3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 73 publications
(109 reference statements)
3
56
0
Order By: Relevance
“…Inactivation of all 3 PHDs is required for a strong and sustained EPO production in the liver (19)(20)(21)(22)(23) ) did not change rbc parameters or induce renal Epo transcription (Supplemental Figure 3). In contrast, Foxd1-Phd2 -/-mutants developed polycythemia.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Inactivation of all 3 PHDs is required for a strong and sustained EPO production in the liver (19)(20)(21)(22)(23) ) did not change rbc parameters or induce renal Epo transcription (Supplemental Figure 3). In contrast, Foxd1-Phd2 -/-mutants developed polycythemia.…”
Section: Resultsmentioning
confidence: 97%
“…While our study identified at least 2 interstitial cell populations in the kidney that displayed differential sensitivity to Phd2 inactivation, inactivation of at least 2 HIF-PHDs is required for moderate Epo induction in hepatocytes. To achieve very high levels of Epo induction in the liver, inactivation of all 3 HIF-PHDs is required (21)(22)(23). The role of individual PHDs in the regulation of EPO in other cell types, however, is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The specialized REPs do not respond to the developing anemia with EPO production. In CKD, the pattern of EPO expression reflects these changes, moving from a pattern of renal predominance to hepatic predominance [48]. …”
Section: The Hif System: Biologic Activity and Regulationmentioning
confidence: 99%
“…Some studies suggest possible role of proximal tubular cells in EPO production (5). In liver, EPO producing cells are hepatocytes and perisinusoidal (Ito) cells (1,6). Synthesis of EPO is hypoxia dependent, and physiological hypoxia appears during high altitude exposure, or strenuous exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of EPO is hypoxia dependent, and physiological hypoxia appears during high altitude exposure, or strenuous exercise. Important role here play hypoxia inducible factors 1 and 2 (HIF 1 and 2) which induce erythropoietin gene transcription (1,6). These are ubiquitary enzymes, but HIF 2 is more present in kidney and liver cells, and hence more specific for EPO gene transcription (7,8).…”
Section: Introductionmentioning
confidence: 99%